Training Play, Storytelling, and Singing (BCM) Methods for Islamic Religious Learning Teachers in Kulon Progo - Setiawan, Iwan; Zuhdi, M Nurdin (Hasil Karya 'Aisyiyah untuk Indonesia, 2026)
Islamic religious studies are often synonymous with memorization and are filled with rigid, unmotivating doctrines. Consequently, Islamic religious studies are often perceived as boring. Therefore, efforts are needed to make Islamic religious studies more enjoyable. Based on this foundation, Islamic religious studies training using the play, story, and singing (BCM) method was conducted. This community service program aimed to improve the pedagogical competence of Islamic religious teachers through BCM (Play, Storytelling, and Singing) method training. The program involved 80 Al-Islam teachers from Muhammadiyah elementary schools in Kulon Progo. A participatory training approach was applied through workshops and practical demonstrations. The results showed increased teacher understanding of active learning strategies and commitment to implementing BCM methods in classroom settings. The program contributed to creating more engaging and meaningful Islamic religious learning.